Cell non-autonomous requirement of p75 in the development of geniculate oral sensory neurons - Tao Tang (Nature Portfolio, 2020)
Abstract During development of the peripheral taste system, oral sensory neurons of the geniculate ganglion project via the chorda tympani nerve to innervate taste buds in fungiform papillae. Germline deletion of the p75 neurotrophin receptor causes dramatic axon guidance and branching deficits, leading to a loss of geniculate neurons. To determine whether the developmental functions of p75 in geniculate neurons are cell autonomous, we deleted p75 specifically in Phox2b + oral sensory neurons (Phox2b-Cre; p75fx/fx) or in neural crest-derived cells (P0-Cre; p75fx/fx) and examined geniculate neuron development. In germline p75−/− mice half of all geniculate neurons were lost. The proportion of Phox2b + neurons, as compared to Phox2b-pinna-projecting neurons, was not altered, indicating that both populations were affected similarly. Chorda tympani nerve recordings demonstrated that p75−/− mice exhibit profound deficits in responses to taste and tactile stimuli. In contrast to p75−/− mice, there was no loss of geniculate neurons in either Phox2b-Cre; p75fx/fx or P0-Cre; p75fx/fx mice. Electrophysiological analyses demonstrated that Phox2b-Cre; p75fx/fx mice had normal taste and oral tactile responses. There was a modest but significant loss of fungiform taste buds in Phox2b-Cre; p75fx/fx mice, although there was not a loss of chemosensory innervation of the remaining fungiform taste buds. Overall, these data suggest that the developmental functions of p75 are largely cell non-autonomous and require p75 expression in other cell types of the chorda tympani circuit.